A fluorine-containing copolyetherimide dielectric film and a method for preparing the same

By introducing fluorine-containing structural units into the polyetherimide backbone and using 6FDA-MPD repeating structural units to improve the conformational rotation resistance of the backbone, the problem of intensified charge injection and migration in pure polyetherimide films at high temperatures was solved, thereby improving the heat resistance and energy storage performance of the dielectric film and achieving enhanced insulation retention and energy storage efficiency at high temperatures.

CN122356477APending Publication Date: 2026-07-10HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610632779.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-09
Publication Date
2026-07-10

AI Technical Summary

Technical Problem

Existing pure polyetherimide films, due to the low rotational resistance of the molecular backbone conformation in high-temperature working environments, result in enhanced thermal motion of chain segments, leading to increased space charge injection and migration, which in turn increases the conductivity loss of the dielectric film, limits the characteristic breakdown field strength, and reduces the energy storage efficiency.

Method used

By introducing fluorinated structural units into the polyetherimide backbone and using a fluorinated copolyetherimide dielectric film, the rigid aromatic imide skeleton and -C(CF3)2- groups in the 6FDA-MPD repeating structural unit are used to increase the conformational rotation resistance of the backbone and enhance the spatial confinement effect of molecular chain motion. Furthermore, the -C(CF3)2- structure is used to change the local electronic environment of the backbone and suppress charge injection and migration at high temperatures.

Benefits of technology

This technology enables the glass transition of the dielectric film to move to the high-temperature region, improving heat resistance and insulation retention at high temperatures. It also synergistically enhances breakdown field strength, discharge energy density, and energy storage efficiency, ensuring cyclic charge-discharge stability and fatigue tolerance under high temperature and strong electric field conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122356477A_ABST
    Figure CN122356477A_ABST
Patent Text Reader

Abstract

This invention discloses a fluorinated copolyetherimide dielectric film and its preparation method. The fluorinated copolyetherimide dielectric film is constructed by introducing fluorinated structural units into the polyetherimide backbone. The molecular backbone simultaneously contains BPADA-MPD repeating structural units and 6FDA-MPD repeating structural units. The aromatic imide backbone and -C(CF3)2- groups increase the conformational rotational resistance of the backbone and enhance the spatial confinement effect of molecular chain motion, causing the glass transition to shift to the high-temperature region. The -C(CF3)2- structure changes the local electronic environment of the backbone and inhibits charge injection and migration. The preparation method includes prepolymerizing MPD and mixed dianhydrides in NMP at a predetermined molar ratio to obtain a polyamic acid casting solution, followed by casting coating and a programmed temperature rise thermal imidization treatment from 80°C to 300°C to obtain the final product. The fluorinated copolyetherimide dielectric film exhibits high characteristic breakdown field strength, high discharge energy density, and long cycle stability at a high temperature of 150°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials and dielectric energy storage technology, specifically to a fluorinated copolyetherimide dielectric film and its preparation method. Background Technology

[0002] Polyetherimide possesses both mechanical and electrical insulation properties. Polyetherimide films are widely used as energy storage elements in film capacitors and dielectric energy storage systems.

[0003] As electrical engineering advances towards higher power density, the operating temperature of dielectric energy storage devices is gradually increasing. Polyetherimide, relying on the aromatic imide ring structure in its molecular backbone to provide basic thermal stability, is used in the manufacture of dielectric energy storage films. In industrial applications, pure polyetherimide films are prepared and processed into thin-film capacitors through a casting process, and integrated into inverters and pulse power systems to perform energy storage and release operations.

[0004] Existing pure polyetherimide films suffer from intensified thermal motion of polymer chain segments in high-temperature operating environments. The main chain of pure polyetherimide molecules contains flexible ether bonds, resulting in low rotational resistance. As the operating temperature increases, the thermal motion of the polymer molecular chain segments intensifies. This thermal motion not only restricts the glass transition of the material to the high-temperature region but also leads to increased space charge injection and migration under the influence of a high-temperature electric field, causing conductive losses and resulting in decreased energy storage efficiency and discharge energy density. Therefore, how to improve the rotational resistance of the polymer main chain conformation and enhance the spatial confinement effect of molecular chain motion at the molecular structure level, thereby suppressing the thermal motion of polymer chain segments under high-temperature conditions and enabling the glass transition of the dielectric film to shift to the high-temperature region, has become a pressing technical problem to be solved in this field. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a fluorinated copolyetherimide dielectric film and its preparation method, which solves the problem that existing pure polyetherimide films, under high-temperature working environments, suffer from increased chain segment thermal motion due to the low conformational rotational resistance of the molecular backbone, which in turn leads to intensified space charge injection and migration, ultimately resulting in increased conductive loss, limited characteristic breakdown field strength, and decreased energy storage efficiency.

[0006] To achieve the above objectives, the present invention provides the following technical solution: The first aspect of the present invention provides a fluorinated copolyetherimide dielectric film. The fluorinated copolyetherimide dielectric film is constructed by introducing fluorinated structural units into the polyetherimide backbone. While maintaining the integrity of the imide backbone structure, the fluorinated copolyetherimide dielectric film simultaneously includes BPADA-MPD repeating structural units and 6FDA-MPD repeating structural units in its molecular backbone.

[0007] The innovative principle of the above scheme is as follows: The 6FDA-MPD repeating structural unit contains a rigid aromatic imide skeleton and a -C(CF3)2- group. The aromatic imide skeleton and the -C(CF3)2- group increase the conformational rotational resistance of the main chain, enhance the steric confinement effect of molecular chain motion, and shift the glass transition of the film to the high-temperature region. The -C(CF3)2- structure has electron-withdrawing effect and steric hindrance, which changes the local electronic environment of the main chain and inhibits charge injection and migration at high temperatures.

[0008] The second aspect of this invention provides a method for preparing a fluorinated copolyetherimide dielectric film. The preparation process employs a two-step route, including a precursor synthesis stage and a thermal imidization film-forming stage. In the precursor synthesis stage, a diamine monomer is dissolved in a solvent to form a solution. A mixture containing fluorinated dianhydride monomers and non-fluorinated dianhydride monomers is added to the diamine solution according to a predetermined ratio for a prepolymerization reaction, yielding a homogeneous polyamic acid casting solution. The diamine monomer used is MPD, and the dianhydride monomer is composed of a mixture of fluorinated and non-fluorinated dianhydrides. The fluorinated dianhydride used is 6FDA, and the non-fluorinated dianhydride used is BPADA. The polymerization solvent is NMP. The molar ratio of MPD to total dianhydride is set to 1:1.02, and the total molar amount of dianhydride is the sum of the molar amounts of 6FDA and BPADA added to the system. By adjusting the percentage content of 6FDA in the total molar amount of dianhydride, the molecular composition of the fluorinated copolyetherimide dielectric film is changed.

[0009] In the thermal imidization film-forming stage, polyamic acid casting solution is coated onto the substrate surface, and a programmed temperature thermal imidization treatment is performed. After heat treatment, the film undergoes water bath peeling and vacuum drying to obtain a fluorinated copolyetherimide dielectric film. The programmed temperature thermal imidization treatment causes the polyamic acid to undergo dehydration and cyclization, forming a stable polyetherimide structure. The specific conditions for the programmed temperature thermal imidization treatment are: 80℃ for 6 hours, followed by 100℃, 150℃, 200℃, 250℃, and 300℃ for 1 hour each, with a heating rate of approximately 2℃ / min.

[0010] This invention provides a fluorinated copolyetherimide dielectric film and its preparation method. It has the following beneficial effects: 1. This invention introduces a 6FDA-MPD repeating structural unit containing a rigid aromatic imide backbone and -C(CF3)2- groups through co-anhydride copolymerization design in the polyetherimide backbone. The aromatic imide backbone and -C(CF3)2- groups increase the conformational rotation resistance of the backbone and enhance the spatial confinement effect of molecular chain motion, thereby suppressing the thermal motion of polymer chain segments under high temperature conditions. Ultimately, this invention achieves the glass transition of the fluorinated copolyetherimide dielectric film to the high temperature region and improves its heat resistance.

[0011] 2. This invention introduces 6FDA-MPD repeating structural units containing -C(CF3)2- groups into the molecular backbone of a fluorinated copolyetherimide dielectric film. By utilizing the electron-withdrawing effect and steric hindrance of the -C(CF3)2- structure to change the local electronic environment of the backbone, the charge injection and migration process at high temperatures is suppressed, and the insulation retention capability is enhanced while reducing high-temperature conductivity loss. Ultimately, this invention achieves a synergistic improvement in the breakdown field strength, discharge energy density, and energy storage efficiency of the fluorinated copolyetherimide dielectric film under high-temperature conditions.

[0012] 3. This invention employs a two-step preparation process comprising a precursor synthesis stage and a thermal imidization film-forming stage. In the prepolymerization reaction, a uniform polyamic acid casting solution is obtained, and the percentage of 6FDA in the total molar amount of dianhydride is adjusted to change the molecular composition of the film. Combined with programmed temperature thermal imidization treatment, the polyamic acid undergoes dehydration and cyclization to form a stable polyetherimide structure. Ultimately, this improves the cyclic charge-discharge stability and fatigue resistance of the fluorinated copolyetherimide dielectric film under long-term working conditions of high temperature and strong electric field. Attached Figure Description

[0013] Figure 1 This is a schematic diagram of the preparation process and synthesis route of the FPI-x thin film of the present invention; Figure 2 The Fourier transform infrared (FTIR) spectra of the PEI and FPI-x films of the present invention are shown below. Figure 3 Nuclear magnetic resonance (NMR) spectra of PEI and FPI-x thin films of the present invention Figure 1 ; Figure 4 Nuclear magnetic resonance (NMR) spectra of PEI and FPI-x thin films of the present invention Figure 2 ; Figure 5 The glass transition temperature (DSC) curves of the PEI and FPI-x films of the present invention are shown. Figure 6 The graph shows the relationship between the discharge energy density and energy storage efficiency of PEI and FPI-x films under 150℃ conditions and the electric field. Figure 7 The Weibull distribution diagram of the breakdown strength of PEI and FPI-x films under 150°C is shown. Figure 8 The graph shows the relationship between the discharge energy density and energy storage efficiency of PEI and FPI-70 films under the conditions of 150℃ and 200MV / m, as a function of the number of charge-discharge cycles. Detailed Implementation

[0014] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0015] Please see the appendix Figure 1-8 This invention provides a fluorinated copolyetherimide dielectric film and its preparation method. The fluorinated codianhydride copolyetherimide dielectric film is constructed by introducing fluorinated structural units into the polyetherimide backbone. The tunable modification of the molecular structure is achieved through co-polymerization design of the fluorinated dianhydride 6FDA and BPADA. While maintaining the integrity of the imide backbone structure, the fluorinated codianhydride copolyetherimide dielectric film simultaneously includes BPADA-MPD repeating structural units and 6FDA-MPD repeating structural units in the backbone. The 6FDA structural unit contains a rigid aromatic imide backbone and -C(CF3)2- groups. The aromatic imide backbone and -C(CF3)2- groups increase the rotational resistance of the backbone conformation, enhance the spatial confinement effect of molecular chain motion, and shift the glass transition of the film to the high-temperature region. The -C(CF3)2- structure possesses electron-withdrawing effects and steric hindrance, altering the local electronic environment of the backbone, suppressing charge injection and migration at high temperatures, and improving the insulation retention capability of the film under high-temperature electric fields.

[0016] The preparation process of the fluorinated codianhydride copolyetherimide dielectric film adopts a two-step route, which mainly includes the following process steps: S1. Precursor synthesis stage: The diamine monomer is dissolved in a solvent to form a solution. A mixture containing fluorinated dianhydride monomer and non-fluorinated dianhydride monomer is added to the diamine solution according to a predetermined ratio to carry out a prepolymerization reaction, thereby obtaining a uniform polyamic acid casting solution.

[0017] S2, Thermal imidization film formation stage: The polyamic acid casting solution is coated onto the substrate surface, and a programmed temperature rise thermal imidization treatment is performed. After the heat treatment, the film is subjected to water bath peeling and vacuum drying to obtain a fluorinated codianhydride copolyetherimide dielectric film.

[0018] The precursor synthesis stage specifically includes: S101. Determine the basic raw materials and solvent components of the polymerization reaction system. The diamine monomer is MPD. The dianhydride monomer is a mixture of fluorinated and non-fluorinated dianhydrides. The fluorinated dianhydride is 6FDA. The non-fluorinated dianhydride is BPADA. The polymerization solvent is NMP. After polymerization, the 6FDA monomer constructs the fluorinated structural unit and the -C(CF3)2- group in the main chain; the BPADA monomer constructs the isopropylidene bridged methyl group in the main chain after polymerization.

[0019] S102. Set the molar ratio of diamine monomer to total dianhydride monomer. The molar ratio of MPD to total dianhydride is set to 1:1.02. The molar amount of total dianhydride is the sum of the molar amounts of 6FDA and BPADA added to the system. Accurately weigh the corresponding amounts of MPD, 6FDA, and BPADA based on the 1:1.02 molar ratio.

[0020] S103. Set the specific proportion of fluorinated dianhydride in the total dianhydride. By adjusting the proportion of 6FDA in the total dianhydride molar amount, six groups of film samples with different component ratios were designed. In the six groups of film samples, the percentage content of 6FDA in the total dianhydride molar amount was set to 0%, 60%, 65%, 70%, 75%, and 80%, respectively.

[0021] S104. Specify the film sample names corresponding to each group's allocation ratio. Film samples without 6FDA monomer are designated PEI. Copolymer film samples containing 6FDA are uniformly designated FPI-x film. The 'x' in the FPI-x film name represents the percentage content of 6FDA in the total dianhydride molar amount. Based on the aforementioned ratios, copolymer film samples containing 6FDA are designated FPI-60, FPI-65, FPI-70, FPI-75, and FPI-80, respectively.

[0022] The thermal imidization film formation stage specifically includes: S201. Dissolve MPD in NMP and stir until completely dissolved under nitrogen protection. Add dianhydride powder in batches slowly to the diamine solution according to the set feeding ratio, and react for several hours under ice bath conditions. Raise to room temperature and continue stirring for 24 hours to obtain a viscous and homogeneous polyamic acid casting solution. Figure 1 The given preparation process involves removing the rotor and performing vacuum degassing on the polyamic acid casting solution.

[0023] S202. The polyamic acid casting solution is uniformly coated onto the cleaned glass plate surface using a coating machine, followed by a programmed temperature-controlled thermal imidization treatment. The specific conditions for the programmed temperature-controlled thermal imidization treatment are: 80℃ for 6 hours, followed by 100℃, 150℃, 200℃, 250℃, and 300℃ for 1 hour each, with a heating rate of approximately 2℃ / min. Figure 1 The given synthetic route involves a programmed temperature-increasing thermal imidization treatment that causes polyamic acid to undergo dehydration and cyclization, forming a stable polyetherimide structure.

[0024] S203. After the heat treatment is completed, the oven is allowed to cool naturally to room temperature. The film is then immersed in deionized water for peeling. The peeled film is dried under vacuum at 80°C for 20 hours to fully remove residual moisture and solvent, finally obtaining a fluorinated codianhydride copolyetherimide dielectric film.

[0025] Fourier transform infrared spectroscopy analysis was performed on the fluorinated codianhydride copolymer polyetherimide dielectric film. In the infrared spectrum of pure PEI film, the peak value at 1778 cm⁻¹ was [missing value]. -1 Position and 1720cm -1 Absorption peaks for both asymmetric and symmetric stretching vibrations of the imide ring carbonyl group appear at positions 1370 cm⁻¹, and an absorption peak for the CN stretching vibration of the imide ring appears at 1370 cm⁻¹. These absorption peaks indicate that a stable imide ring structure is formed in the pure PEI film after heat treatment. The FPI-x film containing 6FDA monomer maintains the same characteristic absorption region of imide as the pure PEI film, indicating that the introduction of 6FDA monomer does not change the basic backbone of the polymer main chain. The FPI-x film shows an absorption peak at 1145 cm⁻¹. -1 The position exhibits the characteristic vibrational absorption peak of the CF bond in the fluorine-containing structural unit, and at 1145 cm⁻¹ -1 The absorption peak intensity at the position gradually increases with increasing 6FDA content. The characteristic vibrational absorption peak of the CF bond indicates that the fluorinated dianhydride unit participates in the polymerization and influences the local chemical environment of the polymer while maintaining the integrity of the imide backbone structure.

[0026] Nuclear magnetic resonance (NMR) analysis was performed on the fluorinated codianhydride copolymer polyetherimide dielectric film. In the ¹H NMR spectrum of pure PEI films, aromatic proton signals were distributed in the 7.9–7.0 ppm region, and characteristic signals of isopropylidene-bridged methyl groups in the BPADA unit were observed at positions 1.7–1.8 ppm. The FPI-x film containing the 6FDA monomer retained the main aromatic proton signal characteristics of the PEI backbone and exhibited a new lower-field absorption signal near approximately 8.0 ppm. The signal intensity at 8.0 ppm gradually increased with increasing 6FDA content, indicating the formation of a new aromatic hydrogen chemical environment in the backbone after the introduction of the 6FDA monomer. 19 In the FNMR spectra, no fluorine signal was detected in the pure PEI film, while fluorine signal peaks were detected in all FPI-x films, and the intensity of the fluorine signal peaks increased with the increase of 6FDA content. The simultaneous presence of isopropylidene-bridged methyl characteristic signals and fluorine signals indicates that the FPI-x films contain both BPADA-MPD repeating structural units and 6FDA-MPD repeating structural units, and the sample composition can be controlled by adjusting the feed ratio.

[0027] The glass transition temperature (GTH) of the fluorinated codianhydride copolymer polyetherimide dielectric films was determined using differential scanning calorimetry (DSC). The results showed that the GTH of the pure PEI film was 221.85 °C. The GTHs of FPI-60, FPI-65, FPI-70, FPI-75, and FPI-80 films were 262.70 °C, 268.56 °C, 270.11 °C, 274.31 °C, and 280.48 °C, respectively. With the increase of the proportion of 6FDA in the total molar amount of dianhydride, the GTH of the dielectric film samples showed a continuous upward trend. Compared to the BPADA unit, the 6FDA structural unit contains a more rigid aromatic imide backbone and a larger -C(CF3)2- group. The aromatic imide skeleton and -C(CF3)2- group increase the resistance to the conformational rotation of the main chain and enhance the spatial confinement effect of molecular chain motion, suppress the thermal motion of polymer chain segments, and cause the glass transition to move to the high temperature region.

[0028] The relationship between the discharge energy density and energy storage efficiency of dielectric films at 150℃ and the electric field was tested. With increasing applied electric field, the discharge energy density of all samples continuously increased, while the energy storage efficiency gradually decreased, indicating that conductivity loss continuously increases in the high-field region at high temperatures. Compared to pure PEI films and other FPI-x films, the FPI-70 film exhibits a slower efficiency decay trend in the high-field region and can maintain a higher energy storage efficiency at even higher electric fields. At an efficiency of approximately 90%, the discharge energy density of the FPI-70 film reaches 3.49 J / cm³, corresponding to an operating electric field of 480 MV / m; the discharge energy density of the pure PEI film under similar efficiency conditions is 2.42 J / cm³, corresponding to an operating electric field of 360 MV / m. Under the same high-efficiency constraint, the discharge energy density of the FPI-70 film is approximately 44.2% higher than that of the pure PEI film, corresponding to an increase in operating electric field of approximately 33.3%, indicating that the FPI-70 film possesses a higher usable energy storage level under high-temperature conditions.

[0029] The Weibull breakdown data of dielectric films at 150℃ were statistically analyzed. The characteristic breakdown field strength of pure PEI film was 559.6 MV / m. The characteristic breakdown field strengths of FPI-60, FPI-65, FPI-70, FPI-75, and FPI-80 films were 579.84 MV / m, 612 MV / m, 659.66 MV / m, 628.3 MV / m, and 620.1 MV / m, respectively. Compared with pure PEI film, the characteristic breakdown field strength of FPI-70 film increased by approximately 17.9%. The introduction of an appropriate amount of 6FDA monomer significantly enhanced the insulation retention capability of the film under high-temperature electric fields. The mechanism of improved insulation retention capability lies in the fact that the -C(CF3)2- structure in the 6FDA unit has a strong electron-withdrawing effect and large steric hindrance, which changes the local electronic environment of the main chain and helps to suppress charge injection and migration at high temperatures.

[0030] The cyclic charge-discharge stability of pure PEI film and FPI-70 film was tested at 150℃ and 200 MV / m electric field. After 50,000 cycles, the discharge energy density and discharge efficiency of both film samples showed only slight fluctuations and no obvious attenuation trend, indicating that both film samples have good cyclic stability and fatigue resistance under high temperature and moderate electric field conditions, and that the 6FDA copolymer modification did not sacrifice the cycle life and operational reliability of the film.

[0031] By introducing 6FDA and BPADA monomers to construct a fluorinated codianhydride copolymer polyetherimide dielectric film, a synergistic improvement in the material's thermal properties, high-temperature breakdown performance, and high-temperature energy storage performance was achieved while maintaining the integrity of the polyimide backbone structure. The FPI-70 film exhibits optimal comprehensive performance, possessing high discharge energy density, energy storage efficiency, and breakdown field strength at 150℃, while also demonstrating good cycle stability.

[0032] For the vacuum degassing operation, solution casting coating film formation operation, discharge energy density test, energy storage efficiency test, breakdown field strength test, and Weibull statistical distribution calculation of polyamic acid casting solution, those skilled in the art can use conventional degassing equipment, coating equipment, dielectric performance tester and statistical algorithm. The above-mentioned vacuum degassing, solution casting film formation, dielectric performance test and Weibull statistical calculation are well known technologies in the field, and will not be described in detail here.

[0033] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A fluorinated copolyetherimide dielectric film, characterized in that, Fluorinated copolyetherimide dielectric films are constructed by introducing fluorinated structural units into the polyetherimide backbone. While maintaining the integrity of the imide backbone structure, the fluorinated copolyetherimide dielectric films simultaneously contain BPADA-MPD repeating structural units and 6FDA-MPD repeating structural units in the molecular backbone.

2. The fluorinated copolyetherimide dielectric film according to claim 1, characterized in that, The 6FDA-MPD repeating structural unit contains a rigid aromatic imide skeleton and a -C(CF3)2- group; the aromatic imide skeleton and the -C(CF3)2- group increase the resistance to the conformational rotation of the main chain, enhance the spatial confinement effect of molecular chain motion, and cause the glass transition of the film to move to the high temperature region.

3. A method for preparing a fluorinated copolyetherimide dielectric film as described in claim 1, characterized in that, The preparation process adopts a two-step route, which includes the following process steps: Precursor synthesis stage: The diamine monomer is dissolved in a solvent to form a solution. A mixture containing fluorinated dianhydride monomer and non-fluorinated dianhydride monomer is added to the diamine solution according to a predetermined ratio to carry out a prepolymerization reaction, thereby obtaining a uniform polyamic acid casting solution. Thermal imidization film formation stage: Polyamic acid casting solution is coated on the substrate surface, and a programmed temperature rise thermal imidization treatment is performed. After the heat treatment, the film is subjected to water bath peeling and vacuum drying to obtain a fluorinated copolyetherimide dielectric film.

4. The preparation method according to claim 3, characterized in that, In the precursor synthesis stage, the diamine monomer is MPD, and the dianhydride monomer is composed of a mixture of fluorinated and non-fluorinated dianhydrides. The fluorinated dianhydride is 6FDA, and the non-fluorinated dianhydride is BPADA. The polymerization solvent is NMP. After polymerization, the 6FDA monomer constructs the fluorinated structural unit and the -C(CF3)2- group in the main chain, and the BPADA monomer constructs the isopropylidene bridged methyl group in the main chain after polymerization.

5. The preparation method according to claim 4, characterized in that, In the precursor synthesis stage, the molar ratio of MPD to total dianhydride was set to 1:1.02; the molar amount of total dianhydride was the sum of the molar amounts of 6FDA and BPADA added to the system.

6. The preparation method according to claim 5, characterized in that, During the precursor synthesis stage, the percentage of 6FDA in the total molar amount of dianhydride is set to 60%, 65%, 70%, 75%, or 80%.

7. The preparation method according to claim 4, characterized in that, The specific operation of the precursor synthesis stage is as follows: MPD is dissolved in NMP and stirred until completely dissolved under nitrogen protection; dianhydride powder is slowly added to the diamine solution in batches according to the set feeding ratio, and reacted under ice bath conditions for several hours; the temperature is raised to room temperature and stirring is continued for 24 hours to obtain a viscous and uniform polyamic acid casting solution; the rotor is removed and the polyamic acid casting solution is subjected to vacuum degassing treatment.

8. The preparation method according to claim 3, characterized in that, In the thermal imidization film-forming stage, the polyamic acid casting solution is uniformly coated onto the cleaned glass plate surface using a coating machine, followed by a programmed temperature thermal imidization treatment. The programmed temperature thermal imidization treatment causes the polyamic acid to undergo dehydration and cyclization, forming a stable polyetherimide structure.

9. The preparation method according to claim 8, characterized in that, During the thermal imidization film formation stage, the specific conditions for the programmed temperature rise thermal imidization treatment are: 80℃ for 6 hours, 100℃, 150℃, 200℃, 250℃ and 300℃ for 1 hour each, with a heating rate of approximately 2℃ / min.

10. The preparation method according to claim 3, characterized in that, After the heat treatment is completed, the oven is allowed to cool naturally to room temperature. The film is then immersed in deionized water for peeling. The peeled film is dried under vacuum at 80°C for 20 hours to fully remove residual moisture and solvent, and finally a fluorinated copolyetherimide dielectric film is obtained.